The Confucian-legalist state : a new theory of Chinese history - Zhao, Dingxin (Oxford studies in early empires, 2015)
'The Confucian-Legalist State' proposes a new theory of social change and, in doing so, analyzes the patterns of Chinese history, such as the rise and persistence of a unified empire, the continuous domination of Confucianism, and China's inability to develop industrial capitalism without Western imperialism